2006
DOI: 10.1007/s10803-006-0271-2
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Affective Speech Prosody is Impaired in Asperger Syndrome

Abstract: Many people with the diagnosis of Asperger syndrome (AS) show poorly developed skills in understanding emotional messages. The present study addressed discrimination of speech prosody in children with AS at neurophysiological level. Detection of affective prosody was investigated in one-word utterances as indexed by the N1 and the mismatch negativity (MMN) of auditory event-related potentials (ERPs). Data from fourteen boys with AS were compared with those for thirteen typically developed boys. These results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 73 publications
7
90
2
Order By: Relevance
“…Alternatively, even if the sensory representation is accurate and communicated to the cortex, there may be a disconnect between the cortical centers that modulate other cortical or lower level activity due to reduced inter-hemispheric or long-range connectivity (Baron-Cohen et al 2005;Courchesne and Pierce 2005). Given the known deficits in cortical processing of prosody in children with ASD (Erwin et al 1991;Wang et al 2001;Kujala et al 2005;Korpilahti et al 2006), one may speculate that the disruption in sensory-motor integration observed in the ASD-HIGH group in this study results from deficient cortical inhibition during vocalization via any of these plausible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, even if the sensory representation is accurate and communicated to the cortex, there may be a disconnect between the cortical centers that modulate other cortical or lower level activity due to reduced inter-hemispheric or long-range connectivity (Baron-Cohen et al 2005;Courchesne and Pierce 2005). Given the known deficits in cortical processing of prosody in children with ASD (Erwin et al 1991;Wang et al 2001;Kujala et al 2005;Korpilahti et al 2006), one may speculate that the disruption in sensory-motor integration observed in the ASD-HIGH group in this study results from deficient cortical inhibition during vocalization via any of these plausible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the ASD-HIGH children may register the stimulus appropriately, but because they have relatively poor control over their vocal system, the result is a very large change in voice F 0 . Regardless of sensitivity, abnormal auditory pathway function in general may be responsible for disrupted input into the initial stage of the auditory vocal motor system (Erwin et al 1991;McClelland et al 1992;Klin 1993;Maziade et al 2000;Wang et al 2001;Boddaert et al 2003;Ceponiene et al 2003;Jansson-Verkasalo et al 2003;Rapin and Dunn 2003;Rosenhall et al 2003;Boddaert et al 2004;Gervais et al 2004;Kasai et al 2005;Kujala et al 2005;Lepisto et al 2005Lepisto et al , 2006Korpilahti et al 2006;Tharpe et al 2006). All of these possibilities warrant further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is frequently misplaced (Baltaxe & Guthrie, 1987), suggesting a prosodic disability or functional disorder, or present in excessive or inadequate amounts (Shriberg et al, 2001), suggesting dysprosody. There have been a few imaging studies which indicate that prosody is processed atypically in people with autism: Wang, Dapretto, Hariri, Sigman & Brookheimer (2001) found that nine-year-olds with autism processed prosody differently from control children; Gervais et al (2004) showed that in four adults with autism the voice-selective regions in the superior temporal sulcus failed to be activated in response to voice (as opposed to non-voice) stimuli; Korpilahti (2007) found atypical neural responses to affective prosody in children with Asperger"s syndrome. Although the samples are small, this suggests that the expressive dysprosody may well be associated with the processing atypicality.…”
Section: Dysprosody and Prosodic Disabilitymentioning
confidence: 99%
“…This supposition, however, is implausible, since many clinical studies (e.g., Kawakubo et al, 2007;Korpilahti et al, 2007;Thönnessen et al, 2008, "traditional condition") and nonclinical studies (e.g., Pulvermüller et al, 2008;Röttger, Schröger, Grube, Grimm, & Rübsamen, 2007;Ruusuvirta, Huotilainen, & Näätänen, 2007) contributions of adjacent regions can have the opposite sign; that is, activity in response to congruent rather than incongruent words (Rossell, Price, & Nobre, 2003) can increase in one region and decrease in the other. This makes it difficult to formulate strong predictions concerning the putative type of the N400 obtained in response to affective prosody violations.…”
Section: Topographymentioning
confidence: 99%